On Institutions, Law, and Economic Development: Regarding the 2024 Nobel in Economics to Acemoglu, Johnson, and Robinson - Acciarri, Hugo Alejandro (2024)
This paper provides a very brief overview of the work of Daron Acemoglu, Simon Johnson, and James Robinson, 2024 Nobel laureates in Economics, using their research as a prompt to stress the importance of professional attention to real-world consequences within legal education and scholarship. Acemoglu, Johnson, and Robinson influential analyses, which explore the colonial roots of economic disparity through the persistence of "inclusive" and "extractive" institutions, offer a framework for understanding how historical institutional choices shape contemporary economic outcomes. By showing the role of political and economic institutions in fostering or stalling development, the paper highlights the necessity for legal disciplines to transcend certain kind of dogmatic legal analysis and incorporate a systematic study of institutional impacts. This reflection calls for a broader integration of interdisciplinary and empirical analyses within general legal frameworks, increasing the quality of the research and legal education.